MONSOON TRAWL BAN AND ITS EFFECTS ON THE LIVELIHOOD OF TRAWL LABOURERS: THE CASE WITHVERSOVAFISHING VILLAGE IN MAHARASHTRA - Salim, Shyam S. (Journal of Indian Fisheries Association, 2007)
Indian fisheries sector in view of its potential contribution to national income, nutritional security, employment opportunities, social objectives and export earnings, plays an important role in the socio-economic development of the country. Fisheries sector contributes 4.3o/o to the agricultural GDP and export earnings are presently valued at over INR 68 billion from a volume of 460,000 tonnes. In addition, it provides direct and indirect employment, and dependency for over seven million people in the country. With an estimated production potential of 8.4 million tonnes, the present level of production in the country is 5.9 million tonnes with almost equal contribution from both marine and inland sectors. The estimated fisheries potential from the Indian exclusive economic zone was found to be 3.9 million tonnes. But in spite of the increased efforts in fish production, the catch stagnates around 2.9 million tonnes. The stagnation in catches, mainly due to the overexploitation of dwindling marine resources, forced the government to impart some management measures to regulate the fishery and for the sustenance of the marine resources. The monsoon trawl ban in fisheries was one of the major reforms, which had created a substantial increase in fish production in the past few years. The ban on trawling during monsoon season was introduced in Maharashtra, after a series of studies, from 1992 for a period of 65 days from 10 June to 15 August or N aralipoornima, whichever is earlier. A notable increase in production from the marine sector of the country occurred in the post-ban period. Nevertheless, it had created problems in employment, poverty and income distribution of fishermen during the ban period and was always a matter of unrest between mechanized and traditional sectors of fishing. The aim of this study was to understand the impact of the ban on monsoon trawling in employment pattern, poverty and income distribution of fishermen along the coast of Maharastra. The study was conducted at the Versova fishing village, Mumbai, and provides reflections on the possible impact of monsoon ban in the livelihood and standard ofliving of the fishermen in the state. Keywords: Marine fisheries, monsoon ban, socio-economic development, Maharashtra